Presentation, Clinical Course and Outcome in Hospitalized Patients with Covid - 19: A Retrospective Study - Nida Naseem; Ritwiza Thakur; Rakesh Sadhu; Monika Jindal (AlQalam Journal of Medical and Applied Sciences, 2021)
Aim. Covid - 19 has spread rapidly since first being reported evoking much concern. No cure is known as yet. Methods. We conducted a retrospective study to try to identify factors contributing to mortality at our institute. Results. Out of a total 211 patients, we had 28 deaths (13.2%). Males were slightly more afflicted than females (57%: 43%). Most of the patients were more than 50 years of age (47%). Co-morbidities contributed significantly to mortality. Conclusion. We identified elderly age (> 50 yrs), multiple co-morbidities (diabetes, respiratory and cardiovascular) and a high Neutrophil:Lymphocyte Ratio (> 9) as significantly contributing to mortality.